Prenatal diagnosis of isolated bilateral clubfoot: Is amniocentesis indicated? - Edouard Leyne; Olivia Anselem; Pénélope Jordan; Alexandre J. Vivanti; Alexandra Benachi; Laurent Salomon; Mathilde Jacquier; Jean‐Marie Jouannic; Ferdinand Dhombres; Tatiana Cambier; Jonathan Rosenblatt; Emmanuelle Pannier; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The aim of this study is to evaluate the benefit of cytogenetic testing by amniocentesis after an ultrasound diagnosis of isolated bilateral talipes equinovarus. Material and methods This multicenter observational retrospective study includes all prenatally diagnosed cases of isolated bilateral talipes equinovarus in five fetal medicine centers from 2012 through 2021. Ultrasound data, amniocentesis results, biochemical analyses of amniotic fluid and parental blood samples to test neuromuscular diseases, pregnancy outcomes, and postnatal outcomes were collected for each patient. Results In all, 214 fetuses with isolated bilateral talipes equinovarus were analyzed. A first‐degree family history of talipes equinovarus existed in 9.8% (21/214) of our cohort. Amniocentesis was proposed to 86.0% (184/214) and performed in 70.1% (129/184) of cases. Of the 184 karyotypes performed, two (1.6%) were abnormal (one trisomy 21 and one triple X syndrome). Of the 103 microarrays performed, two (1.9%) revealed a pathogenic copy number variation (one with a de novo 18p deletion and one with a de novo 22q11.2 deletion) (DiGeorge syndrome). Neuromuscular diseases (spinal muscular amyotrophy, myasthenia gravis, and Steinert disease) were tested for in 56 fetuses (27.6%); all were negative. Overall, 97.6% (165/169) of fetuses were live‐born, and the diagnosis of isolated bilateral talipes equinovarus was confirmed for 98.6% (139/141). Three medical terminations of pregnancy were performed (for the fetuses diagnosed with Down syndrome, DiGeorge syndrome, and the 18p deletion). Telephone calls (at a mean follow‐up age of 4.5 years) were made to all parents to collect medium‐term and long‐term follow‐up information, and 70 (33.0%) families were successfully contacted. Two reported a rare genetic disease diagnosed postnatally (one primary microcephaly and one infantile glycine encephalopathy). Parents did not report any noticeably abnormal psychomotor development among the other children during this data collection. Conclusions Despite the low rate of pathogenic chromosomal abnormalities diagnosed prenatally after this ultrasound diagnosis, the risk of chromosomal aberration exceeds the risks of amniocentesis. These data may be helpful in prenatal counseling situations.